Adolescents’ use of online food delivery applications and perceptions of healthy food options and food safety: a cross-sectional study in the United Arab Emirates - Saleh, Sheima T.; Osaili, Tareq M.; Al-Jawaldeh, Ayoub; Hasan, Haydar A.; Hashim, Mona; Mohamad, Maysm N.; Qiyas, Salma Abu; Al Sabbah, Haleama; Al Daour, Rameez; Al Rajaby, Radhiya; Masuadi, Emad; Stojanovska, Lily; et al. (Frontiers in Nutrition, 2024)
Introduction: this cross-sectional study aimed to assess Online food delivery applications (OFDA) usage trends among adolescent users in the United Arab Emirates (UAE), focusing on their perceptions of healthy food options and food safety (n= 532); Methods: sociodemographic information, frequency of OFDA use, factors affecting food choices, and perceptions of healthy food and food safety were investigated. A total perception score was calculated for each participant; Results: most participants used OFDAs weekly (65.4%), favoring fast food (85.7%). Factors like appearance and price drove food choices (65.0%), while taste and cost hindered healthy food orders (29.7% and 28.2%). Younger and frequent users had lower scores for perceiving healthy food, while seeking healthy options was associated with higher scores (p<0.05). Females and those seeking healthy food showed higher food safety scores (p<0.05). Discussion: the study suggests tailored interventions to promote healthier choices and improve food safety perceptions among adolescents using OFDAs in the UAE.